Baru ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG PASCA PEMINDAHAN MAHASISWA IAIN GORONTALO KE KAMPUS 2 (Studi pada Pedagang Kaki Lima di Sekitar Jalan Gelatik Kota Gorontalo) - sofhian fian (Madani: Jurnal Pengabdian Ilmiah, 2023)
Abstract: This study employed the SWOT analysis method by examining data on the growth of Gelatik Street merchants in Gorontalo City. In-depth interviews were conducted with merchants' representatives along Gelatik Street in Gorontalo City to collect data. The survey results indicated that financing, marketing, and information technology systems remain the most significant impediments for Gelatik Street merchants in Gorontalo City. In addition, the government's support for traders was still inadequate, therefore, it must encourage them to engage in scientific development activities in business management, such as business and financial management training. Then, the transfer of Gorontalo IAIN students to Campus II resulted in a drop in trader turnover of around 50 per cent. This was because the bulk of IAIN Gorontalo students had relocated to campus II, which had substantially impacted the decline in street vendor activity. Keywords: Factor Analysis; Traders.